Webtoon Comic Improves Eighth Graders' Mystery Text Comprehension: Komik Webtoon Tingkatkan Pemahaman Teks Misteri Siswa Kelas VIII - Dhea Dwiastuti; Kurnia Febianti; Yuliana (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Reading comprehension is essential for junior high students to engage meaningfully with English texts, especially narrative genres. Specific Background: Mystery narratives, while rich in linguistic features and critical thinking opportunities, often pose challenges due to students’ lack of interest and engagement. Knowledge Gap: While digital media like comics have been explored in language learning, limited research addresses the use of Webtoon specifically for teaching mystery narrative texts in rural educational settings. Aims: This study investigates the effectiveness of using Webtoon comics as a digital medium to improve reading comprehension among eighth-grade students at MTs Negeri 2 Empat Lawang. Results: Using a quasi-experimental design with pre- and post-tests, findings showed the experimental group taught with Webtoon outperformed the control group, achieving a significant gain (mean = 72.36 vs. 67.02; t = 3.454, p = 0.001). Novelty: This research uniquely integrates mystery narrative texts with digital storytelling tools in a rural Indonesian context, targeting specific comprehension skills such as inference and reference. Implications: The findings suggest that digital comics like Webtoon enhance student motivation and comprehension, offering a promising pedagogical strategy aligned with students’ digital habits and literacy development.Highlight : Webtoon comics effectively improve students’ reading comprehension, especially in understanding mystery narrative texts. Statistical analysis confirms a significant difference in post-test scores between experimental and control groups. Digital media integration enhances engagement and supports comprehension through visual storytelling. Keywords : Webtoon Comic, Reading Comprehension, Mystery Narrative, Digital Literacy, Educational Technology